BET Protein Inhibitor JQ1 Ameliorates Experimental Peritoneal Damage by Inhibition of Inflammation and Oxidative Stress - Vanessa Marchant; Flavia Trionfetti; Lucia Tejedor-Santamaria; Sandra Rayego-Mateos; Dante Rotili; Giulio Bontempi; Alessandro Domenici; Paolo Menè; Antonello Mai; Catalina Martín-Cleary; Alberto Ortiz; Adrian M. Ramos; et al. (MDPI AG, 2023)
Peritoneal dialysis (PD) is a current replacement therapy for end-stage kidney diseases (ESKDs). However, long-term exposure to PD fluids may lead to damage of the peritoneal membrane (PM) through mechanisms involving the activation of the inflammatory response and mesothelial-to-mesenchymal transition (MMT), leading to filtration failure. Peritoneal damage depends on a complex interaction among external stimuli, intrinsic properties of the PM, and subsequent activities of the local innate-adaptive immune system. Epigenetic drugs targeting bromodomain and extra-terminal domain (BET) proteins have shown beneficial effects on different experimental preclinical diseases, mainly by inhibiting proliferative and inflammatory responses. However the effect of BET inhibition on peritoneal damage has not been studied. To this aim, we have evaluated the effects of treatment with the BET inhibitor JQ1 in a mouse model of peritoneal damage induced by chlorhexidine gluconate (CHX). We found that JQ1 ameliorated the CHX-induced PM thickness and inflammatory cell infiltration. Moreover, JQ1 decreased gene overexpression of proinflammatory and profibrotic markers, together with an inhibition of the nuclear factor-κB (NF-κB) pathway. Additionally, JQ1 blocked the activation of nuclear factor erythroid 2-related factor 2 (NRF2) and restored changes in the mRNA expression levels of NADPH oxidases (NOX1 and NOX4) and NRF2/target antioxidant response genes. To corroborate the in vivo findings, we evaluated the effects of the BET inhibitor JQ1 on PD patients' effluent-derived primary mesothelial cells and on the MeT-5A cell line. JQ1 inhibited tumor necrosis factor-α (TNF-α)-induced proinflammatory gene upregulation and restored MMT phenotype changes, together with the downmodulation of oxidative stress. Taken together, these results suggest that BET inhibitors may be a potential therapeutic option to ameliorate peritoneal damage.